2019
DOI: 10.1039/c8qi01020j
|View full text |Cite
|
Sign up to set email alerts
|

A potassium thiocyanate additive for hysteresis elimination in highly efficient perovskite solar cells

Abstract: Potassium thiocyanate as a cheap additive effectively eliminates the hysteresis effect of perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…It is clear that the XRD pattern of MT is completely different from those of melamine and KSCN which can be used as evidence for the formation of crystalline MT by the acid-catalyzed reaction between melamine and KSCN. 28,29 The FTIR spectra, displayed in Fig. 1(b), show the N-H stretching and bending vibrations of melamine in the region of 3000-3500 and 1640 cm À1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that the XRD pattern of MT is completely different from those of melamine and KSCN which can be used as evidence for the formation of crystalline MT by the acid-catalyzed reaction between melamine and KSCN. 28,29 The FTIR spectra, displayed in Fig. 1(b), show the N-H stretching and bending vibrations of melamine in the region of 3000-3500 and 1640 cm À1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks between 1433-1533 and 810 cm À1 are assigned to the C-N stretching and bending vibrations, respectively, and the triazine ring vibrations appear at 1021 and 578 cm À1 . 28,29 The KSCN spectrum shows the two characteristic peaks at 2046 and 1641 cm À1 due to C]S stretching and bending vibrations, respectively. 28 However, the MT spectrum shows all the peaks assigned to the C]S, N-H, C-N, and triazine vibrations in addition to two new peaks at 1173 and 655 cm À1 that can be assigned to the C-S stretching and bending vibrations, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To resolve these issues, efforts have been made to modify the metal‐oxide/perovskite interface as well as introducing additives to mitigate ionic defects in the perovskite absorber layer. With respect to the latter, several studies have shown alkali metals (Li, Na, K, Rb, and Cs) introduced as additives in the perovskite precursor solution to increase device performance and reduce hysteresis . Very few studies have introduced these alkali metal salts directly to the interface, where defects predominantly reside.…”
Section: Introductionmentioning
confidence: 99%
“…For another example, with inorganic halide ionic compounds pAssivating CsPbBr 3 NCs before purification with anti-solvent, the up-to-date highest EQE for perovskite NCs has been achieved [6]. Salts containing thiocyanate (SCN) have been demonstrated to be able to increase grain size and reduce defects in perovskite thin film [25] and have shown beneficial effects on stability [26], device performance and suppression of hysteresis in solar cell [27]. SCN, as a kind of pseudohalide, has also presented efficient pAssivation effect on perovskite NCs [28].…”
Section: Introductionmentioning
confidence: 99%